Knowledge, attitudes and risk practices on echinococcosis in Aysén District, Chile - Nicole Sepulveda; Marcela Fresno; Yanina Poblete; Hernan Cañon Jones (One Health)
Echinococcosis, a zoonotic disease caused by Echinococcus granulosus and E. multilocularis, presents significant health and economic challenges globally. This study assessed knowledge, attitudes, and practices regarding cystic echinococcosis in the rural communities, health professionals, and educators of Capitán Prat Province, Aysén Region, Chile. A survey of 243 participants revealed a high general awareness of the disease (81.6 %), with significant variations in knowledge levels and practices across sectors. Risk behaviours, such as allowing dogs to roam freely and improper disposal of animal viscera, were prevalent, particularly in rural areas. While preventive measures, including deworming and education, were highly valued, gaps in their consistent application persisted. The findings underscore the need for targeted educational campaigns and culturally sensitive interventions to address behavioural risk factors. Strengthening One Health initiatives through community engagement and intersectoral collaboration is critical to reducing the burden of hydatidosis in endemic regions.